Room-temperature exceptional plasticity in defective Bi2Te3-based bulk thermoelectric crystals - Deng, Tingting; Gao, Zhiqiang; Li, Ze; Qiu, Pengfei; Li, Zhi; Yuan, Xinjie; Ming, Chen; Wei, Tian-Ran; Chen, Lidong; Shi, Xun (Science (American Association for the Advancement of Science), 2024)
The recently discovered metal-like room-temperature plasticity in inorganic semiconductors reshapes our knowledge of the physical properties of materials, giving birth to a series of new-concept functional materials. However, current room-temperature plastic inorganic semiconductors are still very rare, and their performance is inferior to that of classic brittle semiconductors. Taking classic bismuth telluride (Bi2Te3)-based thermoelectric semiconductors as an example, we show that antisite defects can lead to high-density, diverse microstructures that substantially affect mechanical properties and thus successfully transform these bulk semiconductors from brittle to plastic, leading to a high figure of merit of up to 1.05 at 300 kelvin compared with other plastic semiconductors, similar to the best brittle semiconductors. We provide an effective strategy to plastify brittle semiconductors to display good plasticity and excellent functionality simultaneously.The recently discovered metal-like room-temperature plasticity in inorganic semiconductors reshapes our knowledge of the physical properties of materials, giving birth to a series of new-concept functional materials. However, current room-temperature plastic inorganic semiconductors are still very rare, and their performance is inferior to that of classic brittle semiconductors. Taking classic bismuth telluride (Bi2Te3)-based thermoelectric semiconductors as an example, we show that antisite defects can lead to high-density, diverse microstructures that substantially affect mechanical properties and thus successfully transform these bulk semiconductors from brittle to plastic, leading to a high figure of merit of up to 1.05 at 300 kelvin compared with other plastic semiconductors, similar to the best brittle semiconductors. We provide an effective strategy to plastify brittle semiconductors to display good plasticity and excellent functionality simultaneously.